Synthesis of Smart Packaging from Cellulose Acetate with The Addition of AgNO3 as An Antibacterial Substance - Febryanti, Amalyah; Benu, Marlon; Aferta, Lusi; Siswara, I.M; Mulijani, Sri; Alif, Alfiah (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2024)
Synthesis of smart packaging from cellulose acetate with the addition of AgNO3 as an antibacterial substance has been investigated. The purpose of this study is to fabricate smart packaging from cellulose acetate with the addition of AgNO3 as an antibacterial substance. The method used was solution casting. In addition, this study was also characterizing the smart packaging, they included tensile strength and elongation percent test, antibacterial test, morphology analysis using SEM, and biodegradability test. The plastics obtained were clearly yellow, not easily damaged, a little thick, and the smooth surface and slightly bubbly. The largest tensile strength of plastic was 0.0661 MPa, it found in sample No. 2, while the smallest tensile strength was 0.027 MPa, it found in sample No. 1. The greatest elongation value at break was 5% found in sample No. 4, while the smallest elongation value at break was 3.5% in sample No. 3. The result of antibacterial test reported that the freshest mangoes were shown by samples No. 1 and No. 2; while the fast-rotting mangoes were shown in the sample No. 3 and No. 4. The results of the SEM test showed the presence of nano-sized particles that spreaded in the plastic body. The greatest degradability degree were sample No. 4 about 0.0009 g/day with the percentage of mass loss about 17.38%. Futhermore, cellulose acetate can be used as a basic material for making plastics. The addition of AgNO3 in plastic synthesis can help to delay the process of fruit spoilage caused by bacteria.